Desegregating Chicago's Public Schools Policy Implementation, Politics, and Protest, 1965-1985 - Danns, Dionne; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Highlighting the processes and missteps involved in creating and carrying out school desegregation policies in Chicago, Dionne Danns discusses the challenges of using the 1964 Civil Rights Act to implement school desegregation and the resultant limitations and effectiveness of government legislative power in bringing about social change.
Keywords: Science; Science; Science, general